Open co-ordination as advanced liberal government - Haahr, Jens Henrik (Journal of European public policy, 2004)
This article applies a Foucauldian analytics of government to recent developments in the European Union (EU), focusing particularly on open methods of co-ordination (OMCs) in the EU. It argues that in the perspective of an analytics of government, the open method of co-ordination can fruitfully be understood as "advanced liberal government", a particular conceptualization of government constituted of "practices of liberty". These practices continuously presuppose, depend on and enable their subjects - in the case of the OMC most often the relevant national government agencies. At the same time, however, they shape and reshape them. There is thus a dual nature to the open method which is typical of advanced liberal government: the method enables and opens up new possibilities for its subjects and at the same time restrains these subjects as they are subjected to a certain calculative and disciplinary regime. (Original abstract)